1991
DOI: 10.2307/971780
|View full text |Cite
|
Sign up to set email alerts
|

Late Postclassic Chronology in Western Morelos, Mexico

Abstract: Chronology building is an integral part of the archaeological research process, and changing research questions often require the refinement of existing chronologies. This view is illustrated with a description of the derivation, refinement, and confirmation of a ceramic sequence for the Postclassic period in Morelos, Mexico. The joint application of stratigraphy and quantitative ceramic seriation produced a five-phase Postclassic chronology. To deal with problems in distinguishing the stylistically similar ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 16 publications
0
34
0
Order By: Relevance
“…The use of obsidian hydration as an absolute-dating method remains controversial as reflected by the differences of opinion among authors in the Special Section (also see Smith and Doershuk 1991). In the preceding discussion, we made the assumption that the dates (both radiocarbon and hydration) were correctly determined and, thus, we suggested that discrepancies between the hydration dates, the radiocarbon dates, and the ceramic data might be due to depositional, sampling, and/or cultural (e.g., recycling) factors.…”
Section: Discussionmentioning
confidence: 99%
“…The use of obsidian hydration as an absolute-dating method remains controversial as reflected by the differences of opinion among authors in the Special Section (also see Smith and Doershuk 1991). In the preceding discussion, we made the assumption that the dates (both radiocarbon and hydration) were correctly determined and, thus, we suggested that discrepancies between the hydration dates, the radiocarbon dates, and the ceramic data might be due to depositional, sampling, and/or cultural (e.g., recycling) factors.…”
Section: Discussionmentioning
confidence: 99%
“…This relative chronology was correlated with absolute dates, refined, and expanded to include other central Mexican regions associated with the Aztec Empire as a result of major regional survey and excavation projects beginning in the 1960s (Charlton 1966;Parsons 1966;Blanton and Parsons 1971;Whalen and Parsons 1982;Smith and Doershuk 1991;Evans and Freter 1996;Hare and Smith 1996;Nichols and Charlton 1996;Parsons et al 1996;Hodge 1998;Brumfiel 2005b). Sanders et al (1979) argued that Aztec I and II ceramics were roughly contemporaneous, regional variants used in the Basin of Mexico between AD 1150 and 1350.…”
Section: Postclassic and Colonial Ceramic Chronologies In Central Mexmentioning
confidence: 99%
“…More attention has been given to remains excavated in domestic contexts of a rural settlement, Yautepec, in which local ceramics as well as importations from the valley of Mexico appear (Smith 2006b(Smith , 2007Smith and Doershuk 1991). In the valley of Toluca little systematic research has been done so far (e.g., García Payón 1941;Smith 2001c;Vargas 1975), therefore ceramics from the last centuries before the conquest remain poorly understood.…”
Section: Sources To Study Late Pre-colonial Ceramicsmentioning
confidence: 99%